THE RELATIONSHIP BETWEEN TOXIC WORKPLACE ENVIRONMENTS ON JOB PRODUCTIVITY AND TURNOVER INTENTION - Ismail, Fadillah; Safian, Nur Nadzirah; Kadir, Adibah Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The workplace environment can be defined as relationship of individual at the workplace in term of technical, human and organization. It is classified into two major categories: collaborative and toxic workplace environment. This study is focusing on toxic workplace environment. Thus, this study intention to regulate the relationship between toxic workplace environment on job productivity and turnover intention. Bullying, harassment and incivility were defined as three dimensions of toxic workplace. The objective of this study is to examine the level of toxic workplace environment, to identify the relationship between toxic workplace environment and job productivity and lastly, to determine the relationship between toxic workplace environment and turnover intention. 196 questionnaire forms were distributed to targeted sample comprising top and middle management at one of the state government administrative centers located at Johor Bharu. Collected data were analyzed using Statistical Packages for Social Science (SPSS) software. The findings of the research revealed that, job productivity have no relationship with the three dimensions of toxic workplace environment. Meanwhile, for turnover intention, a toxic workplace environment has negative influence in term of bullying dimension. The finding of his research will be able to assist with the alignment of employees in the field of an organization and will be useful for the future research in this area.